Beyond covariates: an intersectional framework for housing conditions, disability, and health equity - Lutchmie Narine (Frontiers in Environmental Health, 2026)
Background Housing conditions are critical drivers of health disparities, yet traditional scholarship often evaluates socioeconomic variables as isolated covariates rather than intersecting, multiplicative forces. Methods This paper introduces the Intersectional Housing Conditions and Health Equity (IHCHE) framework, a novel four-level model integrating intersectionality and ecosocial theories. To ground this framework, a hybrid narrative review evaluated 280 unique records indexed in Web of Science and Dimensions between 2019 and 2026. Results The synthesis demonstrates the analytical necessity of separating exposures into three independent dimensions: physical quality, tenure security, and structural accessibility. Crucially, a major systemic evidence gap is identified regarding actual housing accessibility for disabled individuals, along with a lack of formal three-way statistical interaction modeling across race, income, and disability. Conclusion The IHCHE framework provides a standardized, actionable roadmap to guide future social epidemiology, quantitative intervention targeting, and environmental justice policy.